Staying Safe Online - Hubbard, Ben , 1973-; Potts, Nikki (Illinios : Capstone Global Library, 2017)
Take a look into the workings of our digital planet! From computer programs and WiFi to hardware and hard drives, this series will take you inside the computer and online world that you use every day.
Includes bibliographical references (page 23) and index.
Keywords: Internet and children -- Juvenile literature; Internet -- Security measures -- Juvenile literature